Gambaran Pelaksanaan Peer Assesment terhadap Perilaku Profesional Mahasiswa pada Pembelajaran Skill di Laboratorium - Isnaeni Rofiqoch; Diah Atmarina Yuliani (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2022)
Professional behavior in midwifery students is one of the competencies that must be possessed, because later midwifery students when they enter the field of work will face patients. Assessment of professional behavior can be assessed by Peers/fellow friends not only by lecturers or Clinical Instructor (CI). The purpose of this study was to determine the description of the implementation of Peer Assessment on the professional behavior of midwifery students in learning skills in the laboratory. The results showed that the indicators for assessing professional behavior obtained results including: responsibility indicators 93.69%, discipline indicators 81.71%, teamwork indicators 97.84%, indicators 97.84%, and indicators 97.77%, while the average percentage of all indicators 1-5 is 93.77%, this value is considered high because it exceeds 90% of 100%. The conclusion of this study is that the assessment of student professional behavior can be carried out by friends using the Peer Assessment method, Peer Assessment can also make students to be more responsible and take it as self-reflection material to see the weaknesses and strengths of the students.